Seasonality of reported tuberculosis cases from 2006 to 2010 in Wuhan, China. (October 2014) - LUO, T.; SUMI, A.; ZHOU, D.; KOBAYASHI, N.; MISE, K.; YU, B.; KONG, D.; WANG, J.; DUAN, Q.
SUMMARY We investigated the seasonality of tuberculosis (TB) in Wuhan, China, to evaluate the increased risk of disease transmission during each season and to develop an effective TB control strategy. We applied spectral analysis to the weekly prevalence data of sputum smear positive (SSP) and sputum smear negative (SSN) pulmonary TB reported from 2006 to 2010. Cases of both SSP and SSN feature 1·0- and 0·5-year periodic modes. The least squares method was used to fit curves to the two periodic modes for SSP and SSN data. The curves demonstrated dominant peaks in spring similar to cases reported previously for other locations. Notably for SSP, dominant peaks were also observed in summer. The spring peaks of SSP and SSN were explained in terms of poorly ventilated and humid rooms and vitamin D deficiency. For the summer peaks of SSP, summer influenza epidemics in Wuhan may contribute to the increase in TB prevalence.